Tree phylogenetic diversity structures multitrophic communities. (6th December 2020) - Staab, Michael; Liu, Xiaojuan; Assmann, Thorsten; Bruelheide, Helge; Buscot, François; Durka, Walter; Erfmeier, Alexandra; Klein, Alexandra‐Maria; Ma, Keping; Michalski, Stefan; Wubet, Tesfaye; Schmid, Bernhard; et al.
Abstract: Plant diversity begets diversity at other trophic levels. While species richness is the most commonly used measure for plant diversity, the number of evolutionary lineages (i.e. phylogenetic diversity) could theoretically have a stronger influence on the community structure of co‐occurring organisms. However, this prediction has only rarely been tested in complex real‐world ecosystems. Using a comprehensive multitrophic dataset of arthropods and fungi from a species‐rich subtropical forest, we tested whether tree species richness or tree phylogenetic diversity relates to the diversity and composition of organisms. We show that tree phylogenetic diversity but not tree species richness determines arthropod and fungi community composition across trophic levels and increases the diversity of predatory arthropods but decreases herbivorous arthropod diversity. The effect of tree phylogenetic diversity was not mediated by changed abundances of associated organisms, indicating that evolutionarily more diverse plant communities increase niche opportunities (resource diversity) but not necessarily niche amplitudes (resource amount). Our findings suggest that plant evolutionary relatedness structures multitrophic communities in the studied species‐rich forests and possibly other ecosystems at large. As global change non‐randomly threatens phylogenetically distinct plant species, far‐reaching consequences on associated communities are expected. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.